2014
DOI: 10.1177/1043659614524792
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Oral Communication for Internationally Educated Nurses

Abstract: Achieving English language proficiency, while key to successful adaptation to a new country for internationally educated nurses (IENs), has presented more difficulties for them and for educators than previously recognized. Professional communication within a culturally diverse client population and maintaining collaborative relationships between nurses and other team members were perceived as new challenges for IENs. Learning an additional language is a long-term, multistage process that must also incorporate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 19 publications
(36 reference statements)
0
50
0
1
Order By: Relevance
“…The above studies indicate that the empowering structures described in Kanter's theory—such as support, information, and informal power—may help IENs adjust to the new work environment. Other studies have also shown how IENs struggle to access information and to communicate in a foreign language (Allan & Westwood, ; Jose, ; Lum, Dowedoff, Bradley, Kerekes, & Valeo, ), cf. Kanter's concept of “access to information,” which concerns managing daily work and organisational information.…”
Section: Theoretical Frameworkmentioning
confidence: 97%
“…The above studies indicate that the empowering structures described in Kanter's theory—such as support, information, and informal power—may help IENs adjust to the new work environment. Other studies have also shown how IENs struggle to access information and to communicate in a foreign language (Allan & Westwood, ; Jose, ; Lum, Dowedoff, Bradley, Kerekes, & Valeo, ), cf. Kanter's concept of “access to information,” which concerns managing daily work and organisational information.…”
Section: Theoretical Frameworkmentioning
confidence: 97%
“…According to nursing researchers (Batnitzky & McDowell, 2011; Lum, Dowedoff, Bradley, Kerekes, & Valeo, 2015), very little academic attention has been paid to the challenges faced by FENs in their working lives. However, there is a growing body of literature pertaining to FENs (Okougha & Tilki, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A lack of the 'right' language skills can also impede successful continuing professional development (Terry, Carr and Williams 2013). The necessary skills involve not only technical competence in written and spoken English, but also social and clinical competence, across different contexts (Lum 2014).…”
mentioning
confidence: 99%
“…the ability to engage in 'small talk' (Holmes and Major 2003) with patients and colleagues, as well as 'the sociocultural aspects of communication as in jokes, sarcasm, euphemisms and non-verbal behaviours' (Kawi, 2009). This includes competency in terms of not just what is said, but also how it is said (Lum 2014). …”
mentioning
confidence: 99%